Penyuluhan Fisioterapi K3 untuk Strategi Preventif dan Promotif Terhadap Nyeri Punggung Bawah di PT Adimitra Baratama Nusantara, Kalimantan Timur - Rizky Dini Utami; Ali Multazam (Pusat Riset dan Inovasi Nasional, 2025)
Background: Low Back Pain (LBP) is one of the most common musculoskeletal health problems. This condition can be caused by various factors, including infections, tissue degeneration, neoplasms, trauma, congenital disorders, metabolic diseases, and autoimmune disorders. Several risk factors increase the incidence of LBP, such as prolonged excessive physical activity, stress, habitual heavy lifting, obesity, and prolonged sitting. Objective: This study aims to measure the effectiveness of occupational health physiotherapy education (K3 physiotherapy) in improving workers’ understanding of LBP and its prevention through education and McKenzie Exercises. Methods: The method involved providing education to 25 workers with evaluations conducted before and after the intervention (pre-test and post-test). Results: The results showed a significant improvement in workers’ understanding following the education, particularly regarding risk factors, symptoms, and preventive exercises. Conclusion: It can be concluded that occupational health physiotherapy education is effective in increasing workers’ awareness of LBP and self-management strategies.